Lateral epicondylitis treatment using mesenchymal stem cells: a narrative review (Research, Society and Development, 2022)
Tendons diseases are frequently seen in clinical practice, even more in athletes. This disease can be accompanied of a disabling musculoskeletal pain, being of a substantial impact in the patients’ lives. Although the diverse ways to treat LE, most of the results are not satisfactory, and there is no evidence of a therapy that is more effective than placebo or no treatment at all. Therefore, throughout the last decades, new perspectives towards LE management appeared, such as mesenchymal stem cells therapy (MSCs), that demonstrated promising results in a fair number of studies. This study presents itself with the purpose to revise the existing literature towards the use of mesenchymal stem cells as a treatment to lateral epicondylitis, summarizing the existing clinical evidences and evaluating its efficacy, as to create a clear vision of the current researches and its progress in such therapy. Revise literature towards the effectiveness of stem cells use in lateral epicondylitis treatment. The review occurred in July, 2022, using original and high scientific evidence level publications in MEDLINE and Cochrane Library databases. Also, the references in which the studies were based, were also analyzed. There were selected five prospective studies that evaluated the efficacy of mesenchymal stem cells in lateral epicondylitis and other tendon diseases. All of the studies concluded that there was a significant recovery of the tendinopathy. Even though the studies show mesenchymal stem cells therapeutic potential toward lateral epicondylitis treatment, the lack o clinical trials makes it difficult to determine what type of transplant should be made, where the cells should come from and how many cells are ideal for clinical use.